The association between neonatal birthweight discordance and preeclampsia in twin pregnancy - Chen, Wei; Li, Zhuyu; Wang, Dongyu; Wang, Zilian (The journal of obstetrics and gynaecology research, 2024)
Purpose To investigate the association between neonatal birthweight (NBW) discordance and preeclampsia (PE) in twin pregnancy. Methods This was a single‐center retrospective cohort study. Women with two live births in the First Affiliated Hospital of Sun Yat‐sen University from January 2011 to June 2020 were eligible. They were classified into four groups based on the quartiles of NBW discordance in monochorionic (MC) and dichorionic (DC) twin pregnancy. The relationship between NBW discordance and the risk of PE was assessed by logistic regression, subgroup analyses was further analyzed. Results A total of 1566 women were eligible for the final analysis, there were 445 MC cases and 1121 DC cases. No matter in monochorionic or dichorionic pregnancy, higher NBW discordance quartiles were associated with increased risks of PE. Compared with women in the lowest NBW discordance quartile, women in the highest NBW discordance quartile had approximately 3.6 and 6.0 times risk of PE in monochorionic and dichorionic pregnancy respectively. The association between quartiles of NBW discordance and the risk of PE were higher in dichorionic pregnancy than in monochorionic pregnancy. No matter in MC or DC pregnancy, no significant interaction effects were identified for maternal age, pregnancy body mass index, mode of conception and whether complicated with gestational diabetes mellitus. Conclusions The increased NBW discordance quartile was related to an increased risk of PE. Assessing estimated fetal weight discordance by using ultrasound in clinical practice to predict PE remained to be further researched.